2014
DOI: 10.1007/s11548-014-1110-0
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic tracking in surgical and interventional environments: usability study

Abstract: EM tracking can provide effective assistance to surgeons or interventional radiologists during procedures performed in a clinical or CBCT environment. Applications in the CT scanner demand precalibration to provide acceptable performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…In general, the measurement errors have nonuniform distributions over the tracking volume [22]. It is therefore necessary to characterize systematic (bias) and random (jitter) errors, in terms of both position and orientation of the sensor.…”
Section: ) Error Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the measurement errors have nonuniform distributions over the tracking volume [22]. It is therefore necessary to characterize systematic (bias) and random (jitter) errors, in terms of both position and orientation of the sensor.…”
Section: ) Error Parametersmentioning
confidence: 99%
“…The ground truth optical tracking observations are then used to determine the tracking error at each location. Alternatively, error characterization could be performed with manual positioning [23], or a calibration phantom [22].…”
Section: ) Error Parametersmentioning
confidence: 99%
“…This assessment protocol employs a machined base plate to measure positional and rotational tracking data, offering simplicity, reproducibility, a high precision ground truth and accuracy. This protocol is now widely considered to be the standard method, but there is the limitation that measurement accuracy is a function of translation or rotation [17]. Optical tracking [16] and robots have also been used, however, these solutions are expensive and typically involve complicated calibration procedures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing popularity of EM tracking in interventional applications, significant tracking errors due to metallic objects (i.e., steel, aluminium and bronze) placed between the emitter and the sensor, and the use of some electronic devices, such as a C-arm unit, have been reported to cause disturbances to the magnetic field below 4.2 mm [8,13,[17][18][19][20]. Such errors can be particularly prevalent in clinical environments and their sources difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown that measurement uncertainty may vary considerably depending on the clinical setup. 7,8 To reduce tracking errors due to environmental interference, some manufacturers deployed direct current (DC) tracking systems. These systems measure the pose of the sensor relative to the transmitter once the magnetic field is stabilized.…”
Section: Introductionmentioning
confidence: 99%